(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article analyzes the significance of the integrative approach in physics education and the pedagogical conditions necessary for its effective implementation. The study examines key factors including national policy and legal frameworks, material and technical resources, curriculum content, digital infrastructure, and instructor qualifications as the fundamental components supporting integrative methodology. The author highlights the integration of theoretical knowledge with laboratory practice, digital tools, and real-life scenarios to enhance students’ practical competence. Specific examples from the "Electricity and Magnetism" course are discussed along with their applicability to other branches of physics.